2011
DOI: 10.1186/1749-7922-6-31
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of surgical treatment of perforated peptic ulcers in Northwestern Tanzania: A tertiary hospital experience

Abstract: BackgroundPerforated peptic ulcer is a serious complication of peptic ulcers with potential risk of grave complications. There is paucity of published reports on perforated peptic ulcer disease in our local environment. This study was conducted to evaluate the clinical presentation, management and outcome of patients with peptic ulcer perforation in our setting and to identify predictors of outcome of these patients.MethodsThis was a combined retrospective and prospective study of patients who were operated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

33
92
5
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(167 citation statements)
references
References 18 publications
(34 reference statements)
33
92
5
9
Order By: Relevance
“…This is comparable to a study in Kenya which reported a duodenal to gastric ulcer ratio of 11.5:1. 6 A high duodenal to gastric ulcer ratio of 25:1 was reported in Sudan. A study in Ghana reported high incidence of gastric ulcer perforations than duodenal ulcer perforation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is comparable to a study in Kenya which reported a duodenal to gastric ulcer ratio of 11.5:1. 6 A high duodenal to gastric ulcer ratio of 25:1 was reported in Sudan. A study in Ghana reported high incidence of gastric ulcer perforations than duodenal ulcer perforation.…”
Section: Discussionmentioning
confidence: 99%
“…In case of perforated PUD ulcer, free intraperitoneal gas is less likely to be seen if the time interval between the perforation and radiological examination in short. 6 Recently, Computerized tomography (CT) scans with oral contrast are now considered the reliable method of detecting small pneumoperitonium before surgery and the gold standard for the diagnosis of a perforation. 6 Abdominal ultrasonography has also been found to be superior to plan radiographs in the diagnosis of free intra-peritoneal air.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is similar to other studies in developing countries but differ from the demographic profile from developed countries where majority of the patient are above 60 years of age. 20 In this study only 26.6% patients had a history of ingested NSAIDs. The high incidence of perforated peptic ulcer occur in male in our study may be due to smoking and excessive alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Overall complications rate in their series were higher than our series. This difference in complication can be explained by differences in antibiotic coverage, meticulous preoperative care and proper resuscitation of the patients before operation, improved 20 anaesthesia and somewhat better hospital environment .…”
Section: Discussionmentioning
confidence: 99%